Predicting the prognosis of undifferentiated pleomorphic soft tissue sarcoma: a 20‐year experience of 266 cases. Issue 9 (30th July 2019) - Vodanovich, Domagoj A.; Spelman, Tim; May, Deborah; Slavin, John; Choong, Peter F. M.
Abstract : Background: Undifferentiated pleomorphic sarcoma (UPS) is a rare malignant tumour of mesenchymal origin, which was conceived following re‐classification of malignant fibrous histiocytoma (MFH). The objective of this study is to determine prognostic factors for the outcome of UPS, following multi‐modal treatment. Methods: Data of UPS tumours from 1996 to 2016 were collected, totalling 266 unique UPS patients. Median follow‐up was 7.8 years. All tumours were retrospectively analysed for prognostic factors of the disease, including local recurrence (LR) and metastatic disease (MD) at diagnosis, tumour size, grade, location and depth, patient age, adjuvant therapy and surgical margin. Overall survival (OS), post‐treatment LR and metastatic‐free survival were assessed as outcomes. Results: The 5‐ and 10‐year OS rates for all ages were 60% and 48%, respectively, with a median survival time of 10.1 years. Multivariate analysis revealed that the adverse prognostic factors associated with decreased OS were older age ( P < 0.001; hazard ratio 1.03) and MD at diagnosis ( P = 0.001; 2.89), with upper extremity tumours being favourable ( P = 0.043; 2.30). Poor prognosis for post‐operative LR was associated with older age ( P = 0.046; 1.03) and positive surgical margins ( P = 0.028; 2.68). Increased post‐treatment MD was seen in patients with large tumours (5–9 cm ( P < 0.001; 4.42), ≥10 cm ( P < 0.001; 6.80)) and MD at diagnosis ( P < 0.001; 3.99), adjuvant therapy was favourable, shown to reduce MD ( P < 0.001; 0.34). Conclusions: UPS is a high‐grade soft tissue sarcoma, for which surgery striving for negative margins, with radiotherapy, is the treatment of choice. Older age, lower extremity location, MD at presentation, large size and positive surgical margins, were unfavourable. Abstract : Undifferentiated pleomorphic sarcoma is a high‐grade soft tissue sarcomas, for which the combination of surgery and radiation therapy is the treatment of choice. Our institution, a tertiary sarcoma referral centre, collated 20 years of undifferentiated pleomorphic sarcoma patient data to determine prognostic factors for the disease. Older age, lower extremity location, metastatic disease at presentation, large size and positive surgical margins, were unfavourable; with adjuvant radiotherapy being shown to reduce both mortality and metastatic spread of disease.